Dilp8 requires the neuronal relaxin receptor Lgr3 to couple growth to developmental timing - Garelli, Andres (2015)
Funding Information: We thank C. Mirth, C. Ribeiro and A. Jacinto for their comments and suggestions; I. Miguel-Aliaga, A. Jacinto, P. Leopold, P. Domingos, C. Mirth, R. Teodoro, M. Dominguez, M.L. Vasconcelos, J.C. Yin and M. O’Connor, for reagents. Stocks obtained from the Bloomington Drosophila Stock Center (NIH P40OD018537) were used in this study. A.M.G., F.H., A.M., A.R.M.D. and T.K. are supported by the FCT, under the FCT Investigator Programme and FCT fellowships SFRH/BPD/94112/ 2013, PD/BD/52421/2013, SFRH/BD/94931/2013 and SFRH/BPD/74313/2010, respectively. A.G. is supported by the CONICET and UNS, and Y.A.V. holds a CONICET fellowship. The work in the laboratory of A.M.G. is funded by the CEDOC and the European Commission FP7 (PCIG13-GA-2013-618847). A.G. thanks N.P. Rotstein and L.E. Politi for providing funds and space to develop a part of this project in their lab. Publisher Copyright: © 2015 Macmillan Publishers Limited All rights reserved.